2016
DOI: 10.17523/bia.v73n2p118
|View full text |Cite
|
Sign up to set email alerts
|

Curva de lactação de fêmeas mestiças Taurino x Zebu

Abstract: Objetivou-se comparar equações matemáticas descritas na literatura, identificar a que melhor descreve a produção de leite e estimar alguns componentes da curva de lactação de vacas de alta variabilidade genética, resultante de cruzamento taurino (Bos taurus) x zebuíno (Bos indicus), em sistema de produção semi-extensivo em Sergipe. Foram utilizados 1496 registros de produção de leite. Os controles leiteiros foram realizados em intervalos de 30 dias no período de 2011 a 2012. O ajuste foi feito para a curva méd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Larger values of the 'a', 'b', and 'c' parameters estimated by WL for Holstein cattle were found by Torshizi et al (2011). However, the results in this study using WL were close to those found by Pereira et al (2016) for cows from Bos taurus taurus x Bos taurus indicus.…”
Section: Breed (Composition)supporting
confidence: 71%
See 2 more Smart Citations
“…Larger values of the 'a', 'b', and 'c' parameters estimated by WL for Holstein cattle were found by Torshizi et al (2011). However, the results in this study using WL were close to those found by Pereira et al (2016) for cows from Bos taurus taurus x Bos taurus indicus.…”
Section: Breed (Composition)supporting
confidence: 71%
“…provide an indication of the nutritional management for each genetic group and the group with the highest probability of achievement of a desired level of milk yield (Hossein-Zadeh 2016). However, the studies about the modeling of lactation curve and its components should be used with caution, because the wrong choice may lead to economical losses (Pereira et al 2016).…”
Section: Breed (Composition)mentioning
confidence: 99%
See 1 more Smart Citation
“…The R 2 aj values were mostly above 0.94 (Table 2), emphasizing the good quality of fit obtained in the present work since R 2 is generally not very high in studies on lactation curves. Pereira et al (2016), for example, found an R 2 aj value equal to 0.86 while using the model of Bianchini Sobrinho to describe the lactation curve of the Bos taurus x Bos indicus cross. Daltro et al (2019) 2); one of the reasons for this is that the expression of the model corresponds to a decreasing straight line, which is not the pattern of a lactation curve.…”
Section: Resultsmentioning
confidence: 99%
“…The use of crossbred animals for milk production requires analysis of performance of individual cows, and the lactation curve is one of the main tools used to predict such performance (Pereira et al, 2016). The main components of the lactation curve are peak yield, time to peak, and persistency of milk yield (Wasike et al, 2014).…”
Section: Introductionmentioning
confidence: 99%